214k views
16 votes
Help please!! Thank you!! :)

Let m = x^2+3
Which equation is equivalent to (x^2+3)^2+7x^2+21=-10 in terms of m?
A. m^2+7m+10=0
B. m^2-7m+10=0
C. m^2+7m+31=0
D. m^2-7m+31=0

User F Perroch
by
4.3k points

1 Answer

9 votes

Answer:

A. m^2+7m+10=0

Explanation:

This is a problem in pattern matching, and in substituting a variable for a pattern.

(x^2+3)^2 +7x^2 +21 = -10 . . . . . . given

(x^2 +3)^2 +7(x^2 +3) = -10 . . . . . factor the last two terms

m^2 +7m = -10 . . . . . . . . . . . . subsitute m for x^2 +3

m^2 +7m +10 = 0 . . . . . . . . add 10 to both sides; matches A

User Kohlerm
by
4.6k points